THE IMPLEMENTATION OF ECO-TECHNO FARMING SYSTEM TO INCREASE FARMER’S INCOME AND REDUCE GREEN HOUSE GASES EMISSION - Tani, Sri Arnita Abu (Journal of Saintech Transfer, 2019)
PKM Program in Kajanglako Farming Group, Pudak Village in Kumpeh Ulu District is not only to produce farmers with independent character and entrepreneur spirit, but also to enable them in saving the environment as well as to increase their income. It has been known that beef cattle’s farming business system always been conducted in a traditional way without any kind of technology creation in waste utilization either in solid or liquid waste. Likewise, the farming business of food crops such as sweet corn (Zea Mays L. Saccarata) or the rice plant always been depending toward the subsidiary fertilizer which the availability of the product is not continuous, the cost has been increasing and affecting the production cost spent by the farmers. By the factors mentioned, it is affecting the business productivity carried by the farmers will not be optimum, greenhouse gases emission like N2O, CH4 dan CO2 are also increasing due to accumulation of beef cattle’s solid and liquid waste and intensive use of chemical fertilizers. Therefore, there is a need to implement eco techno farming system to increase the income and to reduce the greenhouse gases (GHG). Methods that has been used in this system implementation conducted in several activities, like (1) processed beef cattle’s solid and liquid waste into many formulas by adding various waste such as banana stem waste, forage feed leftover, and paddy straw (2) processed beef cattle’s liquid waste into liquid organic fertilizer and Biourine Empon-Empon Extract (3) processed food crop waste into Molasses Probiotic Silage which could be used as a supplement feed for cattle. All of these activities were carried out through outreach and direct application in the field. Various processed waste products such as solid waste and liquid waste beef cattle and crop waste could reduce production costs, and could be a business opportunity to increase revenue and reduce greenhouse gas emissions (GHG).